Determinasi Minat Mahasiswa Dalam Pemilihan Jurusan: Peran Prestasi Akademik - Said, Said; Ibrahim, Misykat Malik; Damayanti, Eka; Salahuddin, Salahuddin (Al-AHYA: Jurnal Pendidikan Biologi, 2025)
The choice of a major in college is a complex academic decision influenced by various factors such as academic achievement, interest, and external motivation. This study explores the relationship between high school learning achievement and interest in choosing a Biology Education major at the State Islamic University (UIN) Alauddin Makassar. This study uses a quantitative approach with an ex post facto method, involving 77 students of the 2017 intake as samples. Data were collected through documentation of report card grades and a questionnaire on interest in choosing a major, then analyzed using descriptive and inferential statistics, including the Pearson correlation test. The results showed no significant relationship between learning achievement in high school and interest in choosing a Biology Education major (significance value = 0.424; p > 0.05). Additional analysis based on gender and school origin also showed no significant differences. These findings indicate that the choice of major is not entirely based on previous academic achievement but can be influenced by other factors such as social influence, family expectations, and career prospects. In addition, around 37.66% of students who choose this major have a low level of interest, which has the potential to affect their motivation and academic success in college. The implications of this study highlight the need for a re-evaluation of the freshman selection process as well as the importance of academic counseling services to ensure students have a better understanding of their academic options.